2022
DOI: 10.1287/mksc.2021.1328
|View full text |Cite
|
Sign up to set email alerts
|

Frontiers: The Persuasive Effect of Fox News: Noncompliance with Social Distancing During the COVID-19 Pandemic

Abstract: Cable news channels—and Fox News in particular—affected the extent to which viewers’ complied with experts’ social distancing guidelines early on in the COVID-19 pandemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
38
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 40 publications
0
38
0
Order By: Relevance
“…Controlled behavioural experiments show that distorted information critically affects people's decision making such as the willingness to cooperate [43]. Recent field evidence finds that during the current COVID-19 crisis, higher exposure to Fox News reduces people's propensity to follow stay-at-home orders [44].…”
Section: Introductionmentioning
confidence: 99%
“…Controlled behavioural experiments show that distorted information critically affects people's decision making such as the willingness to cooperate [43]. Recent field evidence finds that during the current COVID-19 crisis, higher exposure to Fox News reduces people's propensity to follow stay-at-home orders [44].…”
Section: Introductionmentioning
confidence: 99%
“…For the past decade, rising ocean temperatures and increasing numbers of measles outbreaks have had scientists worried about climate change denial and vaccination skepticism [1][2][3]. Yet, the COVID-19 pandemic is an unprecedented demonstration of the immediate threat that science skepticism constitutes to society-whether it is skeptics' neglect of social distancing measures, their protest against a yet to be developed vaccine (as of 2020), or plain disbelief in the existence of the virus [4][5][6]. Critically, these behaviors and beliefs often seem to be accompanied by discussions surrounding the trustworthiness of the expert scientists in charge of countries' responses to the pandemic (such as Dr. Fauci in the United States, Dr. Drosten in Germany, or Dr. Van Dissel in the Netherlands).…”
Section: Introductionmentioning
confidence: 99%
“…5 the first named prominent scientist, and6 the first named prominent novelist.� p < .05 �� p < .01 ��� p < .001 https://doi.org/10.1371/journal.pone.0274379.t002…”
mentioning
confidence: 99%
“…of Fauci and many COVID vaccine efforts. Moreover, previous research has demonstrated the persuasive effects of Fox News on Republican attitudes broadly, as well as on viewers' attitudes toward pandemic guidelines in particular (20,21).…”
Section: Message Considerationsmentioning
confidence: 99%